Probable Risk Factors in Children and_x000D_ Adolescents with Neurodevelopmental_x000D_ and Non-Neurodevelopmental Psychiatric_x000D_ Disorders in a Large Turkish Clinical Sample - (:unkn) unknown (My University, 2019)
Objective: This study is aimed to compare socio-demographic variables, perinatal characteristics, developmental stages, comorbid medical illnesses between children and adolescents with neurodevelopmental psychiatric disorders and non-neurodevelopmental psychiatric disorders.Methods: In this study, the files of 2981 children and adolescents referred to our, childpsychiatry outpatient clinic between January 2015 and September 2016, were examinedretrospectively. The data of DSM 5 based psychiatric diagnosis, mean ages, gender, parentalwork status and education levels, perinatal characteristics, such as a birth week, birth weight,time of speech and walking, frequent comorbid medical conditions such as epilepsy, cardiacdisease and asthma, were obtained.Results: The findings showed that children most often had attention deficit hyperactivitydisorder, and anxiety disorders were the second common health problem. The mean agesand working rates of parents, education level of the mothers were significantly lower in children with a neurodevelopmental psychiatric disorder (n=1502) than children with non-neurodevelopmental disorder (n=690) and no psychiatric diagnosis (n=376) (p<0.05). Youngerage, male gender, the requirement of neonatal intensive care unit, speech and walking delayand presence of comorbid epilepsy were associated with a neurodevelopmental psychiatricdisorder.Conclusion: Knowing socio-demographic, developmental, medical and perinatal variablesassociated with neurodevelopmental and non-neurodevelopmental psychiatric disordersmay help us to develop preventive interventions.

Amaç: Bu çalışmada, nörogelişimsel psikiyatrik bozukluk tanısı alan çocuk ve ergenler ile nörogelişimsel olmayan psikiyatrik bozukluğu olanların sosyodemografik değişkenler, perinatal özellikler, gelişim evreleri ve eşlik eden tıbbi hastalıklar açısından karşılaştırılması amaçlanmıştır._x000D_ Gereç ve Yöntem: Çocuk psikiyatri polikliniğine Ocak 2015–Eylül 2016 tarihleri arasında başvuran 2981 çocuk ve ergenin dosyaları geriye dönük olarak incelendi. DSM 5 temelli psikiyatrik tanı verileri, yaş, cinsiyet, ebeveyn çalışma durumu ve eğitim düzeyleri, doğum haftası, doğum ağırlığı, konuşma süresi ve yürüme gelişimi gibi perinatal özellikler, epilepsi, kalp hastalığı ve astım gibi sık görülen eşlik eden tıbbi durumlar incelendi._x000D_ Bulgular: Çocuklarda en sık dikkat eksikliği hiperaktivite bozukluğu tanısı ve ikinci sıklıkta anksiyete bozuklukları vardı. Nörogelişimsel_x000D_ psikiyatrik bozukluğu (n=1502) olan çocuklarda anne babaların ortalama yaşları, çalışma oranı ve annelerin eğitim düzeyi, nörogelişimsel_x000D_ olmayan psikiyatrik bozukluğu olan (n=690) ve psikiyatrik tanısı olmayan (n=376) çocuklardan anlamlı olarak daha düşüktü (p<0.05). Daha_x000D_ küçük yaş, erkek cinsiyet, yenidoğan yoğun bakım gereksinimi, konuşma ve yürüme gecikmesi ve komorbid epilepsi varlığı nörogelişimsel_x000D_ psikiyatrik bozukluk ile ilişkiliydi._x000D_ Sonuç: Nörogelişimsel ve nörogelişimsel olmayan bozukluklar ile ilişkili sosyodemografik, gelişimsel, tıbbi ve perinatal değişkenleri bilmek,_x000D_ koruyucu müdahaleler geliştirmemize yardımcı olabilir
Geniş Bir Türk Klinik Örnekleminde Nörogelişimsel ve Nörogelişimsel Olmayan Psikiyatrik Bozukluklu Çocuk ve Ergenlerde Olası Risk Faktörleri